Smart molecular probes with controllable photophysical property for smart medicine - Xiaoying Kang; Zekun Du; Shuxuan Yang; Mengyun Liang; Qian Liu; Ji Qi (Smart Molecules)
Abstract Precision medicine calls for advanced theranostics that integrate controllable diagnostic and therapeutic capabilities into one platform for disease treatment in the early stage. Phototheranostics such as fluorescence imaging (FLI), photoacoustic imaging (PAI), photodynamic therapy (PDT), and photothermal therapy (PTT) have attracted considerable attention in recent years, which mainly employ different excited‐state energy dissipation pathways of a chromophore. According to the Jablonski diagram, FLI is related to the radiative process, PAI and PTT are derived from the nonradiative thermal deactivation, and PDT originates from the triplet state energy, in which these processes are usually competitive. Therefore, it is critically important to precisely tune the photophysical energy transformation processes to realize certain diagnosis and treatment properties in optimal state for boosting biomedical applications. Currently, there are mainly two strategies including chemical structure and aggregate behavior changes that relate to the regulation of excited state energy dissipation. In this review, we will discuss the recent advances of smart molecular probes that the photophysical properties can be regulated by external triggers and their applications in biomedical fields. We will summarize the development of activatable phototheranostic molecular probes in response to stimuli such as reactive oxygen species, pH, light, hypoxia, enzyme and gas. The assembly and disassembly of molecular aggregates that greatly affect the photophysical energy transformation processes will also be highlighted. This review aims to provide valuable insights into the development of more accurate diagnostic and therapeutic systems, thereby advancing the emerging field of smart medicine.